600 black spots a pop-up book for children of all ages - Carter, David A. (New York Little Simon/Simon & Schuster Children's Publishing, 2007)
Each page contains an original piece of art work that challenges the reader to find the black spots.
Cover title
Keywords: Counting -- Juvenile literature; Picture puzzles -- Juvenile literature; Toy and movable books; Kinetic sculpture; Picture puzzles; Counting